Disadaptive Manifestations of the Students of Pedagogical Universities and Ways to Overcome Them - Zdanevych, larusa (Pedagogical Discourse, 2012)
The author reveals the theoretical approaches to this problem, interprets the views of other researchers. The author offers the results of own experimental research that confirm the relevance and practical necessity to the research of specific issues.